Pelatihan Pembuatan Komik Edukatif Pencegahan Kekerasan di SD Inpres Lere dengan Bantuan ChatGPT - Ady Irawan; Edy Suparjan; Roni Irawan (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
This training program is designed to instill anti-violent values through visual storytelling in the form of educational comics created by teachers themselves, adapted to the cultural context and environment of students. This initiative stems from the need for teachers to have engaging, relevant, and effective learning media to prevent violence in elementary schools. The Service Learning (SL) method integrates academic learning with social services, emphasizing direct experience through activities such as designing, discussing, and practicing the skills taught. The training begins with an introductory session on the forms and dynamics of violence in elementary schools, followed by an introduction to comics as a medium for communicative learning. The next stage is comic-making training, in which participants design stories grounded in anti-violence values, covering the following themes: norms in everyday life, anti-bullying, peaceful conflict resolution, the courage to report, deliberations on forming a violence-prevention team, and the character "BOWO" as an anti-violence ambassador. The pre-test results showed that teachers' initial abilities were in the adequate category, with an average score of 38–43. Teachers had strengths in visual creativity, but remained weak in plot development and the use of digital applications. The training process was conducted through hands-on practice, demonstrations, and intensive mentoring, enabling participants to master technical skills ranging from script writing and character design to integrating violence-prevention messages and using digital technology in the creative process. The post-test after the training showed significant improvement with an average score of 80–90, or a good category. A gain score of 0.685 indicated a strong and effective training impact. Overall, the training program was shown to increase teachers' empowerment in producing educational anti-violence comics that are engaging, contextual, and applicable. The resulting comics are expected to serve as a strategic medium for building a positive culture, strengthening student character, and minimizing the potential for violence in elementary education environments.